Some Wild Mushrooms of Rupandehi District, West Nepal - HP Aryal; U Budhathoki (Bibechana, 2013)
This mycological investigation carried out at natural as well as community managed forest, of Rupandehi district, western terai and siwaliks region of Nepal. Samples were collected in different area ranging between 90 and 1229 masl in tropical deciduous riverine forest, to subtropical deciduous hill forest. This paper highlights on common wild mushrooms Amanita chepangiana, Geastrum fimbriatum, Macrolepiota procera, Pycnoporus cinnabarinus, Schizophyllum commune, Scleroderma bovista and Sparassis crispa. The collected samples represented seven species of Basidiomycetes belongs to four order and seven families. The specimens were deposited in the Tribhuvan University Central Herbarium, (TUCH), Kathmandu, Nepal.